2018
DOI: 10.1007/s00204-018-2181-4
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctanoic acid (PFOA) exposure promotes proliferation, migration and invasion potential in human breast epithelial cells

Abstract: Despite significant advances in early detection and treatment, breast cancer remains a major cause of morbidity and mortality. Perfluorooctanoic acid (PFOA) is a suspected endocrine disruptor and a common environmental pollutant associated with various diseases including cancer. However, the effects of PFOA and its mechanisms of action on hormone-responsive cells remain unclear. Here, we explored the potential tumorigenic activity of PFOA (100 nM–1 mM) in human breast epithelial cells (MCF-10A). MCF-10A cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…The biological plausibility is supported by limited yet consistent cell‐based mechanistic studies. For instance, the exposure of PFOS at 1–10 μM stimulated in a dose‐dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF‐10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53 . The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co‐exposed to an ER receptor inhibitor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The biological plausibility is supported by limited yet consistent cell‐based mechanistic studies. For instance, the exposure of PFOS at 1–10 μM stimulated in a dose‐dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF‐10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53 . The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co‐exposed to an ER receptor inhibitor.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, the exposure of PFOS at 1-10 μM stimulated in a dose-dependent manner the proliferation, migration and invasiveness of immortalized BC cells MCF-10A, through the upregulation of CDK4 and downregulation of p27, p21 and p53. 23,24 The authors did not find any alteration of ERα and ERβ levels; nonetheless, the cell proliferation was partially blocked when cells were co-exposed to an ER receptor inhibitor. On this regard, the authors suggested other alternative mechanisms contributed to explain the effects triggered by PFOS such as the pathway involving the growth factor receptor EGFR/HER2.…”
Section: Modelmentioning
confidence: 96%
“…In vitro, the ability of PFAS to influence cell proliferation, particularly in assays of breast and other endocrine mediated cells and tissues has been assessed. PFOA and PFOS both increased proliferation, cell migration and invasion of normal human breast epithelial cells and altered the expression of proteins involved in cell cycle regulation, including cyclin dependent kinase 4 [202,203]. Similarly, in a mixture with two other chemicals found in consumer products, environmentally relevant concentrations of PFOA increased cell proliferation in non-malignant breast cancer cells through cell cycle disruption, reduced cell apoptosis and increased estrogen receptor alpha levels [204].…”
Section: Alters Cell Proliferation Cell Death or Nutrient Supplymentioning
confidence: 97%
“…PFOA Association: [61] Association: [202]; [204]; [205]; [207]; [209] Long-chain PFAS a PFOS Association: [203]; [207]; [208]…”
Section: Epidemiological Animal Biosassay In Vitromentioning
confidence: 99%
“…PFOA has also been detected in the blood in several industrialized countries. Exposure to PFOA may be associated with several adverse effects, and recent epidemiological studies have linked its toxicity to tumorigenic processes in the liver, pancreas, breast and testicles (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%